From the Battlefield dispatches of a World War II marine - Levin, Dan 1914- (Naval Inst. Press, 1995)
As a war memoir this short book combines a high order of combat journalism with poetry composed in pauses in the midst of battle, notebook writings too personal to have become dispatches, and a compelling narrative that binds these threads together. It differs from many war memoirs in its reflective look at the imperatives of war, its struggle for meaning, and its final affirmative conclusions.
Keywords: Levin, Dan; Levin, Dan -- 1914-; United States. -- Marine Corps -- Biography; USA -- Marine Corps; Weltkrieg (1939-1945); War correspondents -- United States -- Biography; World War, 1939-1945 -- Personal narratives, American; World War, 1939-1945 -- Campaigns -- Pacific Area; Pazifikkrieg -- 1941-1945; Pazifischer Raum; USA; Autobiografie -- 1943-1945; Erlebnisbericht